Hematological and Biochemical Parameters in Prepubescent Water Buffaloes (Bubalus bubalis) - Toro, M.; Telera, G.C.; D’Aurelio, N.; Sacchini, F.; Ferri, N.; Rossi, E.; Perletta, F.; Tittarelli, M.; Giansante, D.; Massis, F. De (Journal of Buffalo Science, 2023)
Water buffaloes are bred in Europe, Australia, North America, South America, and some African countries. European water buffaloes are all of the river type and are considered to be of the same breed named the Mediterranean water buffalo. This species plays a key role in milk production in Italy. Buffalo breeding for milk production has represented an important economic value in recent years, even in Italian regions where this activity was not historically rooted. Therefore, it is very important to monitor animal health and welfare by performing periodical clinical examinations combined with different hematological and biochemical tests. However, there are few studies regarding these aspects, as well as research aimed at establishing the reference ranges for species. This study aims to define hematological and biochemical parameters in a population of healthy water buffalo in controlled conditions for over a year in Italy.